Circadian influence on metabolism and inflammation in atherosclerosis - McAlpine, Cameron S. (Circ Res, 2016)
Many aspects of human health and disease display daily rhythmicity. The brain’s suprachiasmic nucleus, which interprets recurring external stimuli, and autonomous molecular networks in peripheral cells together set our biological circadian clock. Disrupted or misaligned circadian rhythms promote multiple pathologies including chronic inflammatory and metabolic diseases like atherosclerosis. Here, we discuss studies suggesting that circadian fluctuations in the vessel wall and in the circulation contribute to atherogenesis. Data from humans and mice indicate that an impaired molecular clock, disturbed sleep and shifting light-dark patterns influence leukocyte and lipid supply in the circulation and alter cellular behavior in atherosclerotic lesions. We propose that a better understanding of both local and systemic circadian rhythms in atherosclerosis will enhance clinical management, treatment and public health policy.